2005
DOI: 10.1508/cytologia.70.275
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Heavy Metals and Gibberellic Acid on Mitotic Activity and Some Metabolic Changes of Vicia faba L. Plants

Abstract: SummaryThe influence of gibberellic acid, two heavy metals (cadmium and lead) and their interactions on mitotic activity and biochemical constituents of Vicia faba yielded seeds was studied. The results showed that different concentrations of cadmium (Cd) and lead (Pb) induced marked inhibition in the contents of soluble carbohydrate, proteins and ribonucleic acid. Heavy metals also induced marked increases of the total percentage of abnormalities. Moreover, different types of chromosomal aberrations were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
(5 reference statements)
3
10
0
Order By: Relevance
“…Similarly, other scientists also reported the potentiality of GA 3 in alleviating the detrimental effect of metals hence proves its beneficial role in acclimatizing metal stress on Arabidopsis and Lupin [ 47 ]. Furthermore, GA 3 treatment greatly increased protein as compared to Cd treated plants as reported earlier [ 48 ].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, other scientists also reported the potentiality of GA 3 in alleviating the detrimental effect of metals hence proves its beneficial role in acclimatizing metal stress on Arabidopsis and Lupin [ 47 ]. Furthermore, GA 3 treatment greatly increased protein as compared to Cd treated plants as reported earlier [ 48 ].…”
Section: Discussionsupporting
confidence: 78%
“…It was postulated that the decrease in biomass was a consequence of change in the plant water status accompanied by disturbances in biological and physiological processes such as mitotic activity, photosynthesis, respiration, and mineral nutrition. Nickel accumulation decreased water uptake or enhanced water loss, both of which may produce membrane damage (El-Enany et al, 2000;Mansour & Kamel, 2005). Our results demonstrated that maize plants cv.…”
Section: Discussionsupporting
confidence: 53%
“…In accordance, GA3 is known to counteract the adverse effects of heavy metals (Cd and Pb) on mitotic index and some metabolic mechanisms, e.g. in bean plants (Mansour and Kamel ). No effect of the single and the triple metal combination on ABA levels was observed both in roots and shoots (Table ), highlighting that AUXs and CKs were the hormones specifically affected by the metals.…”
Section: Discussionmentioning
confidence: 99%
“…Control 1.000 ± 0.047 c 1.000 ± 0.047 a 1.000 ± 0.233 a 1.000 ± 0.387 ab 1.000 ± 0.116 a 1.000 ± 0.261 a 1.000 ± 0.289 ab 1. and some metabolic mechanisms, e.g. in bean plants (Mansour and Kamel 2005). No effect of the single and the triple metal combination on ABA levels was observed both in roots and shoots (Table 1), highlighting that AUXs and CKs were the hormones specifically affected by the metals.…”
Section: Rootsmentioning
confidence: 91%